Evaluating Digital Transformation Pathways an Their Influence on SME Market Outcomes: A PRISMA – Based Systematic Evidence - A’isy Fiklil Nafisah; Sudarmiatin Sudarmiatin; Agus Hermawan (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Digital transformation has become a major driver in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the era of global competition. However, scientific evidence regarding the pathway of digital transformation and its impact on market performance remains separately distributed and has not been systematically synthesized. This study conducts a Systematic Literature Review (SLR) based on PRISMA 2020 on international publications within the 2013–2024 range. The results of the analysis indicate that the digital transformation pathway encompasses digital capability, digital orientation, digital integration, digital strategy alignment, and the utilization of operational technology. Each pathway contributes differently to market outcomes such as sales growth, customer retention, market expansion, and competitive advantage. The study also found the presence of moderating and mediating roles through innovation capability, dynamic capability, organizational culture, and competition intensity. This research produces an integrated conceptual model and recommendations for a further research agenda to deepen strategic management theory in the context of MSMEs.